COVID-19: A learning moment for patients and health professionals - Stefano Leccardi (Qualitative Research in Medicine & Healthcare)
A hospital physician from Northern Italy describes his own experience as caregiver of COVID-19 patients and as a patient himself who required treatment in urgent care. From this experience he learned that an untapped reserve of human solidarity exists in a team of caregivers in the midst of a crisis where they find an unsuspected shared energy. He never would have believed to be able to work long hours patiently and without sleep until he was challenged by the demands of the COVID crisis. As such, he discovers that to be effective the team leader should lead by example rather than by commandments! His experience as a patient allowed him to face his own mortality, to learn that healing rather than cure is the ultimate goal of caregiving.